Income distribution and poverty in Portugal [1994/95] : A Comparison between the European Community Household Panel and the Household Budget Survey - Rodrigues, Carlos Farinha (2010)
The aim of this study is to give a broad picture of the income distribution and the level of inequality and poverty in Portugal as revealed by the two most recent family surveys produced by the Portuguese Statistical Office: the European Community Household Panel and the Household Budget Survey. The results obtained consistently point to a very unequal distribution of income, with high levels of inequality associated with high poverty rates. These main findings are not influenced by the choice of survey, revealing a high degree of consistency between the two sources.